Return Autocorrelations and Volatilities of Kuala Lumpur Shariah Compliance that Coincide with Big News in Malaysia - Helma Malini (Management and Sustainable Development Journal, 2021)
This paper investigates the long term return behyavior of Kuala Lumpur Shariah Compliance. This studies relies on two major time series investigation techniques, namely Econometric Modeling of returns; The Autoregressive model, Assumption of Linearity, Volatility Modeling of GARCH and its extension. The statistical process from linearity and volatility modeling, stock return predictability and Shari’ah compliance integration by using GARCH model specification showed that in term of return behaviour particularly volatility of Shari’ah compliances in Malaysia are vulnerable towards events and news that happened in Malaysia.